Multidisciplinary Management of Complicated Crown-Root Fracture of an Anterior Tooth Undergoing Apexification - Mese, Merve (Case Rep Dent, 2015)
The purpose of this case report was to present the multidisciplinary management of a subgingival crown-root fracture of a patient undergoing apexification treatment. A 12-year-old male patient was referred to the pediatric dentistry clinic with an extensive tooth fracture of the right permanent maxillary lateral incisor. Clinical and radiographic examinations revealed the presence of a complicated crown-root fracture, which had elongated to the buccal subgingival area. The dental history disclosed that the apexification procedure had been started to be performed after his first trauma experience and he had neglected his appointment. The coronal fragment was gently extracted; endodontic treatment was performed; flap surgery was performed to make the fracture line visible. The coronal fragment was reattached to the root fragment with a dual-cure luting composite. A fiber post was stabilized and the access cavity of the tooth was restored with composite resin. At the end of the 24th month, the tooth was asymptomatic, functionally, esthetically acceptable and had no periapical pathology. It is important for the patients undergoing apexification treatment to keep their appointments because of the fracture risk. Restoration of the fractured tooth by preparing retention grooves and a bonding fiber-reinforced post are effective and necessary approaches for successful management.